Acerca de la necesidad metafísica del hombre en el pensamiento de Schopenhauer: desde la negación de la Voluntad a la propuesta de una metafísica natural (2016)
Throughout the development of Arthur Schopenhauer’s thought, there are various moments of refection that tell us about the origins, bases and limits of metaphysical thinking. From his first publication on philosophy, Schopenhauer understands existence based on the marked pessimism of his theory of the “will to live” and puts forward the need to deny it. Later on, following Kant, in the volumes of The World as Will and Representation, the thinker will propose that the metaphysical is a basic necessity for man, whose pressing concerns are answered by religions and philosophies in different ways. Both religion and philosophy, however, given the limitations of our conditioned knowledge, can only give us an approximation to that which is transcendent, never certainty or evidence. Only intuition can give us access to the best metaphysical explanation possible and it is from that starting point that humanity will find in its diverse metaphysical expressions a crosscutting and timeless knowledge that feeds both religions and philosophical systems. Starting from the essay About the Metaphysical Necessities of Man, this study seeks to relate both stages of Schopenhauer’s philosophy: the establishment of the philosophy of will and the affirmation of natural metaphysics.